Pieniądz w "Historia religiosa" autorstwa Teodoreta z Cyru - Milewski, Ireneusz (Vox Patrum, 2018)
The paper analyses the reports regarding money, which appear in the Historia religiosa writen by Theodoret of Cyrus. Historia religiosa, on the one hand, presents the life of the Syrian monks, and the other hand depicts the realities of everyday life of the inhabitants of the collapsed provinces of the Roman East at the turn of the fourth and fifth century. On this occasion, we also find in Historia religiosa numerous references to the role of money in everyday life. In the work of Theodoret money appears in several contexts: as an important element of trade on the market, as taxes, as a ransom paid for releasing captives but also as a money in welfare activities (amounts of money donated to charity). Unfortunately, in Historia religiosa, we didn’t found any information about the prices and wages. The analyzed reports, despite a certain lack of precision, are a valuable sources of knowledge. They depicts everyday life in eastern provinces, “stories” unknown to the “great history”, allowing for a reconstruction of social and economic history of the later Roman Empire.